EKSISTENSI TUHA PEUT DI KECAMATAN KLUET TENGAH TERHADAP PEMBENTUKAN RANCANGAN QANUN GAMPONG: Eksistensi Tuha Peut Terhadap Pembentukan Rancangan Qanun - Ridha Mellyza; Hasnul Arifin Melayu; T. Surya Reza (Journal of Indonesian Comparative of Syari'ah Law, 2025)
Tuha Peut is the gampong legislative body which has a large authority and role in gampong government and is also the keuchik working partner in running the government. One of the positions of the Tuha Peut institution in gampong level government is compiling and formulating gampong Qanun. In this case, Tuha Peut also has a role in formulating gampong qanun which are in accordance with South Aceh Regency Qanun Number 22 of 2012 concerning the Duties and Authorities of Tuha Peut as the gampong deliberative body. This means that Tuha Peut was given the authority to draft the village Qanun. This study applies a field-based approach with an empirical legal framework research show that Tuha Peut Kluet Tengah played a role in making the gampong Qanun and preserving gampong customs.